Implementasi Kebijakan Penanggulangan HIV/AIDS (Studi Implementasi Peraturan Daerah Nomor 14 Tahun 2008 tentang Penanggulangan HIV/AIDS di Kabupaten Malang) - Rizzana, Sylfia (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2017)
The phenomenon of HIV/AIDS in Malang is a problem that cannot be underestimated, especially with the number of HIV/AIDS case is increasing dramatically every year. In the latest data says that the current spread of HIV/AIDS in Malang has been evenly distributed in all districts, it is certainly trigger a big question because since 2008 Malang has had specific policies governing HIV/AIDS on Regulation No. 14 2008. With their policy regarding HIV/AIDS in Malang Regency, raises question about how the implementation of policies in countering HIV/AIDS by law No. 14 of 2008 in countering HIV/AIDS in Malang Regency.